Playbook for designing and implementing picture-based insurance - Ceballos, Francisco; Aredo, Samson Dejene; Gaur, Pushkar; Kannan, Samyuktha; Kramer, Berber; Pattnaik, Subhransu; Waweru, Carol (Digital Impact Exchange, 2024)
Picture-Based Insurance is a new, innovative way of delivering affordable, comprehensive, and easy-to-understand crop insurance. By relying on visible crop characteristics derived from farmers’ own smartphone pictures, it aims to minimize the costs of loss verification and detect damage at the plot level, making crop insurance more attractive and accessible to small farmers. This playbook walks the interested reader through all the steps necessary to implement a PBI model from scratch, including product design, product distribution, in-season monitoring, and damage estimation and claim settlement.